The effect of sleep hygiene training given to epilepsy patients on seizure frequency and sleep quality: pre-test post-test control group experimental study protocol - Gelin, Dilek; Oğuz, Sıdıka (International Journal of Clinical Trials, 2024)
Background: Epileptic seizures develop with hyper-synchronization of neuronal networks, causing insomnia, and sleep quality decreases with drug treatment. Insomnia, which occurs with decreased sleep quality, increases epileptic seizure discharges. This study/trial aims to determine the effect of sleep hygiene education given to epilepsy patients on seizure frequency and sleep quality. Methods: It is non-pharmacological clinical research and was conducted experimentally with a pretest-posttest control group experimental model. Randomization was done using simple random selection. The routine treatment of the first experimental group (n=80 people) continued. Patients were provided with sleep hygiene training, a sleep hygiene training booklet, and an educational video for those who requested it. In the three-month follow-up, sleep hygiene training was repeated in the monthly meetings. The second group, the control group (n=80), continued routine treatment, and no intervention was made for three months. In the planned monthly meetings, sleep quality was evaluated using the PSQI (Pittsburgh sleep quality index). In the monthly meetings, the seizure schedule recorded by the patients and the frequency of seizures were evaluated together with the patients. Results: In this study, data collection began on June 1, 2023, and the data collection process ended on May 21, 2024, while the data analysis process is ongoing. Conclusions: With this trial/study, the evidence-based use of sleep hygiene education's effectiveness on the seizures and sleep quality of epilepsy patients will be evaluated. Trial registration: The trial was registered in clinical trials: (ClinicalTrials.gov Identifier: NCT06352476). Registered on: 10881-669.